THE FIELD PRACTICE EVALUATION OF MAGELANG CHRISTIAN 2 VOCATIONAL SCHOOL - Adi Kristianto; Ade Iriani; Wasitohadi Wasitohadi (Universitas Pendidikan Ganesha, 2019)
This study aims to evaluate the field work practice program (PKL) at the Christian Vocational High School 2 Magelang. This research is qualitative evaluative research, the technique of data collection is done by: observation, interview and documentation, this research uses the CIPP model (context, input, process, product). The results of the study are: (a) aspects of the context: this field work practice program is needed by students of the Christian 2 Vocational School of Magelang, the quality of students is very necessary. One way to improve the quality and achievement of students is through the PKL program; (b) input aspects: supporters of the PKL program are with implementation plans, schedules, implementation mechanisms, teachers, staff, funding, facilities and infrastructure both in schools and in the industrial world; (c) process aspects: Magelang 2 Christian Vocational School implements PKL programs in accordance with the regulations of the Directorate of Vocational High Schools. Where the process of implementing PKL program must be carried out well and involve students participating in PKL, schools and the industrial world as a place to carry out PKL; (d) product aspects: the field work practice program at Magelang Christian Vocational High School 2 Magelang proved to be useful for improving students skills and achievements.Keywords: program evaluation, field work practices (PKL), CIPP.